Genetically low vitamin D concentrations and myopic refractive error: a Mendelian randomization study. (6th June 2017) - Cuellar-Partida, Gabriel; Williams, Katie M; Yazar, Seyhan; Guggenheim, Jeremy A; Hewitt, Alex W; Williams, Cathy; Wang, Jie Jin; Kho, Pik-Fang; Saw, Seang Mei; Cheng, Ching-Yu; Wong, Tien Yin; Aung, Tin; et al.
Abstract: Background: Myopia prevalence has increased in the past 20 years, with many studies linking the increase to reduced time spent outdoors. A number of recent observational studies have shown an inverse association between vitamin D [25(OH)D] serum levels and myopia. However, in such studies it is difficult to separate the effects of time outdoors and vitamin D levels. In this work we use Mendelian randomization (MR) to assess if genetically determined 25(OH)D levels contribute to the degree of myopia. Methods: We performed MR using results from a meta-analysis of refractive error (RE) genome-wide association study (GWAS) that included 37 382 and 8 376 adult participants of European and Asian ancestry, respectively, published by the Consortium for Refractive Error And Myopia (CREAM). We used single nucleotide polymorphisms (SNPs) in the DHCR7, CYP2R1, GC and CYP24A1 genes with known effects on 25(OH)D concentration as instrumental variables (IV). We estimated the effect of 25(OH)D on myopia level using a Wald-type ratio estimator based on the effect estimates from the CREAM GWAS. Results: Using the combined effect attributed to the four SNPs, the estimate for the effect of 25(OH)D on refractive error was −0.02 [95% confidence interval (CI) −0.09, 0.04] dioptres (D) per 10 nmol/l increase in 25(OH)D concentration in Caucasians and 0.01 (95% CI −0.17, 0.19) D per 10 nmol/l increase in Asians. Conclusions: The tight confidence intervals on our estimates suggest the true contribution of vitamin D levels to degree of myopia is very small and indistinguishable from zero. Previous findings from observational studies linking vitamin D levels to myopia were likely attributable to the effects of confounding by time spent outdoors.